GAYA BAHASA PERBANDINGAN DAN PERTENTANGAN DALAM NOVEL MATAHARI KARYA TERE LIYE DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA - dan Leli Triana, Ronita, Tri Mulyono, (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2022)
This research study aims to describe the comparative and contradictory language styles found in the novel Matahari by Tere Liye and to describe the implications of research results in learning in high school. This research approach uses a qualitative approach so that the presentation uses an informal method. Data collection techniques used are reading and note-taking techniques. The results of this study indicate that the comparative and contrasting language style in the novel Matahari by Tere Liye produces 54 data citations with descriptions of comparative language style including: simile as much as 5 data, metaphor as much as 1 data, personification as much as 18 data, depersonification as much as 6 data, allegory as much as 7 data, pleonasm/ tautology as much as 1 data, prolepsis/ anticipation as much as 2 data, and contradictory language styles include: hyperbole as much as 8 data, litotes as much as 1 data, irony as much as 4 data, and cynicism as much as 4 data. The implication of the results of this study is that it can be used as an alternative teaching material in Senior high school, especially class XII semester 2 in subject of identifying the elements of novel building. Keywords: Comparative Language Style, Contrasting Language Style, Novel, and Implication.